Postgraduate Distance Education in University of Cape Coast, Ghana: Students’ Perspectives - Andoh, Raphael Papa Kweku; Appiah, Robert; Agyei, Paul Mensah (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
The study explored perceptions of postgraduate distance education students of University of Cape Coast (UCC). Specifically, associations between UCC postgraduate distance students’ characteristics and satisfaction, as well as students’ perceptions of physical facilities, staff-students relationship, facilitator quality, and student support services were examined. Determinants of students’ satisfaction regarding physical facilities, staff-students relationship, facilitator quality, and student support services were also investigated. A census was used for the study, whereby a questionnaire was used to collect data from 125 students. It was revealed that satisfaction was not dependent on age, gender, or programme of study but was significantly related to study centre location and semester of study. The students were generally satisfied with physical facilities, staff-students relationship, and facilitator quality but were unimpressed with student support services. The three domains that students were impressed with were deemed to be determinants of their satisfaction. It was recommended that those aspects of the programme that received satisfactory responses should be maintained but improved on with time. Those aspects with unfavourable responses, on the other hand, were to be critically considered for immediate improvement.